2022
DOI: 10.1002/viw.20220031
|View full text |Cite
|
Sign up to set email alerts
|

Versatile MXene integrated assembly for piezoresistive micro‐force sensing

Abstract: MXenes have received tremendous attention for flexible electronics owing to their excellent conductivity, water dispersibility, and mechanical flexibility. However, the sediment from the MXene production process is usually discarded as trash, resulting in low utilization. Here, we present a flexible pressure sensor that enables micro-force sensing and efficient utilization of MXene by confining MXene trash among structured MXene electrodes. Benefiting from the synergistic effect of both the confined micro-coni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…From the scanning electron microscopy (Figure S6, Supporting Information) and X‐ray diffraction pattern (Figure S7, Supporting Information), it can be seen that the blocky MAX has been successfully exfoliated into layered MXene, as subsequently demonstrated by the Tyndall effect observed in the MXene nanosheets solution (Figure S8, Supporting Information), which is favorable for spraying. [ 48 ] Furthermore, the TEM image (Figure 2b) indicates that the lateral dimensions of MXene nanosheets are several hundred nanometers and the crystal structure is hexagonal. [ 49 ] Before spraying, the BIS film was treated with oxygen plasma to enhance its hydrophilicity (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…From the scanning electron microscopy (Figure S6, Supporting Information) and X‐ray diffraction pattern (Figure S7, Supporting Information), it can be seen that the blocky MAX has been successfully exfoliated into layered MXene, as subsequently demonstrated by the Tyndall effect observed in the MXene nanosheets solution (Figure S8, Supporting Information), which is favorable for spraying. [ 48 ] Furthermore, the TEM image (Figure 2b) indicates that the lateral dimensions of MXene nanosheets are several hundred nanometers and the crystal structure is hexagonal. [ 49 ] Before spraying, the BIS film was treated with oxygen plasma to enhance its hydrophilicity (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…(F) Response and recovery curve of flexible sensing device based on MXene/PDA at P = 0.36 kPa, (G) linear sensitivity at a wide pressure range of 0.18–6.20 kPa, (H) the detailed durability performance under a pressure of striking. (I) Comparison of pressure‐sensitive responses of flexible pressure sensor 16,34–41 …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3F, the MXene/PDAbased flexible sensor exhibits fast response/recovery speeds of 100 and 50 ms, respectively. Because the spherical structure of PDA has good deformation performance, PDA is easy to be affected by external pressure, the current 16,[34][35][36][37][38][39][40][41] changes greatly, and when the external force is withdrawn, the process of PDA deformation recovery is very fast, so the pressure will cause the rapid deformation of the composite membrane. The fast response and recovery capabilities ensure timely and flexible sensing under the action of external forces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3i compares the sensitivity obtained in this study with that reported in the literature. [14,32,33,[37][38][39][40][41][42] Compared with other MXene-based flexible sensors, MXene/PDA-based pressure sensors generally exhibit higher sensitivity, such as MXene/PVB-based porous composite sensor (S 1 =11.9 kPa -1 , S 2 =1.15 kPa -1 , S 3 =0.20 kPa -1 ), Ti 3 C 2 Tx/PVDF-TrFE-based composite nanofiber sensor (0.51 kPa -1 ), elastic microstructure-based MXene/PDMS thin film sensor (S 1 =2 kPa -1 , S 2 =0.003 kPa -1 ) MXene@CS@PU-based pressure sensor (3 kPa -1 ), pressure sensor based on MXene/Cotton (12.095 kPa -1 ), pressure sensor based on MXene/PI (22.32 kPa -1 ), thin-film sensor based on LS-MXene/PVA (S 1 =5.5 kPa -1 , S 2 =1.5 kPa -1 ), elastic aerogels of MXene/rGO (22.56 kPa -1 ) and pure MXene-based thin film sensor. In addition, the response and reply times of our proposed sensor are shorter than those mentioned above, enabling higher-accuracy detection.…”
Section: Resultsmentioning
confidence: 99%